FTIR and Chemometrics Application on Determination of Total Flavonoid Content of Pasak Bumi Root Extract (Eurycoma longifolia Jack.) - Liling Triyasmono; Ana Ulfah; Muhammad Ikhwan Rizki; Khoerul Anwar; Totok Wianto; Heri Budi Santoso (Journal of Pharmascience, 2020)
The combination of FTIR and chemometrics is an alternative method on determination of total flavonoid content of pasak bumi (Eurycoma longifolia Jack.) root extract. This study aims to determine the method of FTIR and chemometrics can be used for determination of total flavonoid content and determine the total flavonoid content of E. longifolia root extract using FTIR and chemometrics. The samples from three growing area were determined their flavonoid content by colorimetric method and measured their absorbance by FTIR spectrophotometer. The analysis was done by PCA chemometrics to grouping IR spectra based on growing area and PLSR to determine prediction model of total flavonoid content of E. longifolia root extract. The best grouping and prediction model is shown by IR spectra in the range of wavenumbers 1800-1540 cm-1 with  total variation is 99%  and prediction model with equation y = 0.995x + 0.002 (R2 calibration = 0.995; R2 validation = 0.970; RMSEC = 0.008; RMSECV = 0.021). The total flavonoid content of E. longifolia root extract (% b/b ± SD) from Mandiangin, Condong, and Sabuai is 0.225 ± 0.009; 0.437 ± 0.007; and 0.466 ± 0.016 (R2 = 0.995 and RMSEP = 0.008). Based on this, the combination of FTIR and chemometrics can be used to predict the total flavonoid content of unknown E. longifolia root extract